The Upper Bound of Information Diffusion in Code Review - Dorner, Michael (Blekinge Institute of Technology, 2023)
More details on https://github.com/michaeldorner/information-diffusion-boundaries-in-code-review
Keywords: Software engineering; Software Engineering; Programvaruteknik